Operational Modeling of Green Hydrogen Production in Sugarcane Biorefineries Considering Electricity Price Variability - Julia Bahia Hufnagel Cavalcante; Fernando Luiz Pellegrini Pessoa (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study evaluates green hydrogen production from surplus electricity in sugarcane biorefineries, considering partial electrolyzer operation as a function of electricity price. A techno-economic model was developed to estimate the Levelized Cost of Hydrogen (LCOH) under different electricity price scenarios. The results indicate that electricity cost is the main driver of LCOH, accounting for approximately 45% of total annual cost under low-price conditions and reaching values close to 80% in high-price scenarios. Distinct operational regimes were identified, with full electrolyzer utilization at low electricity prices (0.04–0.06 R$/kWh), resulting in LCOH between 10.7 and 11.8 R$/kg, and reduced operation at higher prices, leading to a sharp increase in costs. A critical electricity price range between 0.10 and 0.16 R$/kWh was identified, above which the economic viability of green hydrogen deteriorates significantly. Although competitive with values reported in the literature for green hydrogen, the results indicate limited competitiveness compared to grey hydrogen and closer proximity to blue hydrogen costs under favorable conditions. Overall, the findings highlight the potential of the Brazilian sugarcane sector for decentralized green hydrogen production under low-cost electricity conditions.